KAJIAN TRANSPORTASI PERIODE ENAM JAM TERHADAP FREKUENSI PULSUS, NAFAS DAN SUHU TUBUH PADA SAPI PERANAKAN ONGOLE ( P.O. ) - , BAYU VERIANTO, Prof.Dr. drh. Pudji Astuti, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In Indonesia the central high beef consumption is still located around urban areas, whereas beef cattle production centers in the region are still rural. Therefore, to fulfil the demand of meat supply, cattle transportation was needed, but transportation can potentially make cattle become stressed. Transportation stress will trigger an increase in the frequency of breathing, pulsus and body temperature. This study aims to analyze the stress response that PO cows are experiencing due to long distance transportation. This research was conducted using six female cows and five male cows. Physiological data retrieval breathing, and body temperature pulsus was done while cattle rest, 6 hours and 2 days after transport. The results obtained show that the average pulsus when cattle rest is 74,00 times per minute, 6 hours after transport 48,5 times per minute, and 2 days after transport was 71,33 times per minute. The average breath at rest is 18,33 times per minute, 6 hours after the transport 17,83 times per minute, and 2 days after transport was 18,66 times per minute. The average body temperature at rest was 38,4 times per minute, 6 hours after transport 39,3 times per minute, and 2 days after the transportation was 38,7 times per minute. Based on the observations it can be concluded that: (1) transport for six hours caused a decrease in the frequency of breathing and pulsus while temperature increased, (2) pulsus, breathing and body temperature can be used as an indicator of stress.